Klasifikasi Emosi Tokoh Utama Dalam Novel 00.00 Karya Ameylia Falensia Dengan Teori David Krech - Cahyaning Widya Utami; Lutfitri Novitasari; Eva Dwi Kurniawan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study was conducted to analyze the classification of emotions of the main character in the novel 00.00 by Ameylia falensia using David Krech”s theory. The purpose of this tudy is determine the emotional structure of the main characters in the novel that is the object of research. The concepts of gulit, seld-punishment, shame, hatred, and love become the main quotes in the novel 00.00 by Ameylia Falensia. The results showed that the main character in the novel experienced a wide range of emotions related to family problems and events. This study uses a comprehensive literary research methology to identify the emotional structure of the main characters and clasisify the emotions of the main characters in the novel that became the object og research. Thus, it can be concluded that the emotion of all Lengkara characters that is dominant arises in Lengkara, namely the emotion of sadness wich leads to aspects of losing something important to cause disappointment. While the less dominant emotion appears in Lengkara, namely the emotion of the concept of guilt which is characterized by aspects contrary to ethics and moral values.